THE IMPLEMENTATION OF GAME BASED LEARNING FOR CHILDREN - Feny Nida Fitriyani (UIN Sultan Maulana Hasanuddin Banten, 2017)
The 21st century requires education to continue creating the young generation who have life skills so that they can survive and compete in the global community. Education as a media to build superior young generation must give innovation in learning activities. Learning which is various and creative is able to attract learners interest. One of the interesting learning is game based learning. Game based learning is divided into five, they are language game based learning, Music game based learning music, Motion game based learning, Color game based learning, and Logic game based learning. Those five types of game based learning must be designed accordance with the suitable subject.